Qualitative views of Nigerian school principals and teachers on the barriers and opportunities for promoting students’ physical activity behaviours within the school settings (2021)
Background: Insufficient physical activity (PA) is a growing public health challenge among Nigerian adolescents. Significant information gap exists on the school-related factors which influence the participation of adolescents in school-based physical activity programmes in Nigeria. This study was conducted to document the qualitative views of school principals and teachers on the barriers and opportunities for promoting the physical activity behaviours of adolescents within the school settings in light of the socio-ecological model. Methods: This was a qualitative study conducted in 12 public and private schools in two local government areas of Oyo state, Nigeria. Two key sources and data collection methods (i.e key informant interviews and focus group discussions) were used. Six key informant interviews were held with school principals and six focus group discussions with classroom teachers using pre-tested guides. Data was analysed using thematic analysis. Results: Fourteen sub-themes were identified as barriers to PA and linked to different levels of the socio-ecological model. Three themes were categorised as parental factors, three themes as socio-cultural and religious factors while the school-related factors had eight sub-themes. Specifically, the school-related barriers were the declining numberof trained physical health education teachers, limited opportunities for continuing education and low prioritisation of physical health education. Other school-related factors such as increasing demand for classroom academic time, negative attitudinal dispositions of other teachers and inadequate funding for schools which hampered the provision of facilities and equipment were identified as factors that limit the effective implementation of policies and programmes for physical activity in schools. Opportunities to promote PA within the school settings during assemblies, breaktime, after-school and inter-house sports competition exist. However, these opportunities are hampered by competing academic time, security threats, fear of causalities to students due to poor supervision after school, poor funding and brawling associated with competitive school-based sporting events. Conclusions: Factors that contribute to insufficient physical activity among in-school adolescents in the school settings are multi-factorial. Implementation of holistic, multi-component interventions which address the social-cultural and school-level factors and enhance students’ opportunities for physical activity in schools are recommended.